Effect of zinc source and dose and chromium supplementation on performance and carcass characteristics of feedlot cattle - Budde, Ashley Marie, author; Engle, Terry E., advisor; Wagner, John J., advisor; Myrick, Christopher A., committee member (Colorado State University. Libraries, 2018)
Four-hundred cross-bred steers were utilized in a randomized complete block design to investigate the effect of supplemental Zn source and concentration and Cr supplementation on performance and carcass characteristics of feedlot steers fed a steam-flaked corn-based finishing diet. Steers were blocked by initial BW with in cattle source and randomly assigned within block to 1 of 5 treatments (10 steers/pen; n = 8 pens per treatment). Prior to the initiation of the experiment, trace mineral supplement sources were analyzed for Zn and Cr. Zinc and Cr concentrations of the Zn sources were used to balance all dietary treatments to obtain correct Zn and Cr experimental doses. Treatments consisted of: 1) 90 mg Zn/kg DM from ZnSO4 and 0.25 mg Cr/kg DM from Cr propionate (90ZS+Cr); 2) 30 mg Zn/kg DM from Zn hydroxychloride and 0.25 mg Cr/kg DM from Cr propionate (30ZH+Cr); 3) 90 mg Zn/kg DM from Zn hydroxychloride and 0.25 mg Cr/kg DM from Cr propionate (90ZH+Cr); 4) 60 mg Zn/kg DM from ZnSO4 and 30 mg Zn/kg DM from Zn methionine (90ZSM); and 5) 90 mg Zn/kg DM from Zn hydroxychloride (90ZH). Steers were individually weighed on d-2 and on two consecutive days at the end of the experiment. Initial liver biopsies were obtained from all steers during processing. Equal numbers of pen replicates per treatment were transported to a commercial abattoir on d 162, 176, and 211 and slaughtered; individual carcass data and final liver samples were collected. Total finishing dietary Zn and Cr concentrations were 118.4, 58.2, 114.2, 123.0, and 108.2 mg Zn/kg DM and 0.711,0. 647, 0.731, 0.767 and 0.521 mg Cr/kg DM, for treatments 1 to 5, respectively. There were no treatment main effects for any response variables measured. However, treatment was a significant source of variation for certain response variables when single degree of contrasts (unprotected F-test) were performed. Steers receiving 90ZH+Cr had greater final BW (P ≤ 0.04) and ADG (P ≤ 0.03) when compared to steers receiving 90ZH. Additionally, hot carcass weight was 8.5 kg greater (P ≤ 0.03) for 90ZH+Cr compared to 90ZH supplemented steers. Steers receiving 90ZH+Cr had greater longissimus muscle area when compared to steers receiving 90ZSM. Dry matter intake, G:F, final liver Zn concentrations, and all other carcass parameters (dressing percentage, marbling score, yield grade, subcutaneous adipose tissue depth, and KPH) were similar across treatments. These data indicate, that under the conditions of this experiment, Zn source and concentration had no impact on live performance, liver mineral Zn concentrations, and carcass characteristics. Supplemental Cr in diets containing 90 mg of supplemental Zn/kg DM may improve final BW, ADG, and hot carcass weights.
Keywords: chromium; beef cattle; zinc